Política doméstica e política internacional: a institucionalidade da política brasileira de comércio exterior - Andrade, Pedro Henrique Gandra Pia de (2011)
This dissertation examines the degree of institutionality of the Brazilian Foreign Trade Policy, focusing on the role played by CAMEX in the design and control over the policies governing Brazilian foreign trade. The institutional model adopted under the scope of the liberalizing reforms of the early l990s led to flexible institutions, capable of accommodating the different interests and agendas of the federal public administration sectors that shape foreign trade policy, directly and indirectly. The hypothesis suggested becomes apparent as we analyze the evolution of the performance of CAMEX over the past two decades, and the institutional transformations it underwent. The analysis also shows that this institutional architecture built over the CAMEX system was unable to undertake the necessary adjustments to allow for the Brazilian foreign trade to accompany the process of increasing sophistication and dynamism of international trade. As a result, although there have been advances in absolute terms regarding trade facilitation, in relative terms Brazil has lost ground to other countries that have been able to implement such reforms at a faster pace